2018
DOI: 10.21037/tau.2018.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Role of androgens for urethral homeostasis

Abstract: BackgroundWe observed that patients with hypogonadism are at higher risk to experience artificial urinary sphincter cuff erosion. Sphincter erosions have been found to be associated with urethral atrophy or compromised urethras subsequent to events limiting its blood supply. We therefore analyzed possible mechanisms how a decrease in testosterone serum levels can result decreased urethral blood flow.MethodsIn a cohort of >1,200 urethroplasties, tissue specimens obtained during surgeries were analyzed for expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…[14][15][16][17][18][19][20] A study in castrated rats that underwent urethroplasty showed that supplementation with both testosterone and estrogen increased periurethral vascularization after surgery in supplemented rats compared with nonsupplemented rats. 21 Our analysis did not find any evidence that estrogen levels were related to US. However, in adult men, estrogen levels are uniformly low, making it difficult to identify differences.…”
Section: Sex Hormones In Tissue Homeostasiscontrasting
confidence: 61%
“…[14][15][16][17][18][19][20] A study in castrated rats that underwent urethroplasty showed that supplementation with both testosterone and estrogen increased periurethral vascularization after surgery in supplemented rats compared with nonsupplemented rats. 21 Our analysis did not find any evidence that estrogen levels were related to US. However, in adult men, estrogen levels are uniformly low, making it difficult to identify differences.…”
Section: Sex Hormones In Tissue Homeostasiscontrasting
confidence: 61%
“…This study reinforces our initial observation that patients with low serum testosterone levels have a nearly three‐fold higher risk for AUS cuff erosion compared to eugonadal men. The association between LT and urethral fragility appears to validate the foundational concept that androgens are an important contributor to urethral homeostasis 11 . While we suspect that LT potentiates ischemic changes in the periurethral tissues, LT has also been associated with chronic inflammation within the lower urinary tract 14,15 …”
Section: Discussionmentioning
confidence: 64%
“…The association between LT and urethral fragility appears to validate the foundational concept that androgens are an important contributor to urethral homeostasis. 11 While we suspect that LT potentiates ischemic changes in the periurethral tissues, LT has also been associated with chronic inflammation within the lower urinary tract. 14,15 The overall AUS cuff erosion rate observed in this tertiary referral center study is 26.1%, higher than the 5%-13% erosion range typically described in the literature.…”
Section: Aus Cuff Erosion In Lt Patientsmentioning
confidence: 94%
See 2 more Smart Citations